Hydraulic Conductivity Study In Engineered Soil Media For Stormwater Runoff Treatment In Bioretention Facility - Takaijudin, Husna (2017)
The conventional method of drainage system was seemed inadequate to cater urban stormwater runoff due to the drastic increment of the urban population. It was limited to the structural approach which related to hydraulic and hydrologic influence. Hence, this approach has been shifted to more holistic approaches by considering the environmental needs. The revised guidelines of Urban Stormwater Management for Malaysia (MSMA) in 2012 was introduced in-line with the current practices to tackle the urban and sub-urban stormwater issues. Bioretention is a favourable practice which mimics natural processes, integrating the sciences and engineering knowledge of hydrology, hydraulics as well as environment into one system. This research aimed to investigate the interaction between soil hydraulic parameter; mainly saturated hydraulic conductivity (Ksat) and water quality treatment performance and to benchmark Ksat based on bioretention performance. The comprehensive data set required for the study was obtained from a series of standard laboratory tests, designated column studies and field investigation. For this purpose, three (3) soil columns were constructed in Physical Laboratory and Modelling, River Engineering and Urban Drainage Research Centre (REDAC), USM. Four (4) soil configurations and one (1) hydrologic parameter were tested for soil column studies: engineered soil mixtures, media depths, compost materials, mulch layers and inflow variation. Both Ksat and pollutant concentration were examined for influent and effluent samples for each soil configuration. Two (2) field bioretention cells were constructed by applying the best treatment condition from soil column studies by the assistance of vegetation. Ksat and treatment performance data were monitored during nine (9) actual storm events as well as the application of six (6) cycles of synthetic stormwater runoff. Analysis of soil media through soil column studies showed that Ksat values achieved the recommended ranges were reduced over the time which is consistent with the literature. Besides, it is sufficient to treat physical, biochemical and nutrient contaminants from Class IV to Class II above 85% of pollutant removal through sedimentation, adsorption and filtration processes based on the comparison using ANOVA. The results of multiple linear regression (MLR) analyses indicate that removal performance of TSS, TP and other water quality parameters is a function of the Ksat relative (Krel) at most soil configurations with R2 obtained more than 0.8. The study showed that compost material is the main factor that influenced the Ksat values through the relationship between the combinations of water quality parameters. However, the relationship between both parameters varies for field studies confirming that external factors such as duration and size of bioretention, rainfall, and seasonal change had influenced the results.